Durability of technologies in the keeping of ZEB's performances. (August 2018) - Danza, Ludovico; Belussi, Lorenzo; Guazzi, Giulia; Meroni, Italo; Salamone, Francesco
Abstract: Durability is an important aspect that has not to be neglected in ZEB design. The requirements for buildings energy needs reduction and increase of renewable energy sources stimulated designers to integrate technologies in an efficient way. This ambitious goal must meet the capacity of the technical solutions to guarantee their performances over the years. The durability of materials and technologies is a topic that warrants further analyses in order to assess the proper efficiencies and the expected lifetime of a ZEB. Typically the energy balance of a ZEB is calculated by considering the annual energy flows or rarely the whole life cycle. The most used approaches consider constant performance of materials and technical elements over the lifespan. However, the performance loss of a single element can cause an imbalance in the behavior of a ZEB, for which persists a thin balance between inlet and outlet flows. The paper provides a critical point of view on this issue paying attention on the following technical solutions implemented in a case study for which the current scientific literature provides analysis on the degradation during their lifetime: glazing systems, VIPs, PV panels and GSHPs.